Serum zinc as a biomarker to predict the efficacy of immune checkpoint inhibitors in cancers - Jingliang Wang; Weihao Wang; Bin Liu; Rui Zhao; Jing Zhao; Fengxian Jiang; Wei Xu; Zhizhao Zhang; Pancen Ran; Yang Shu; Yahui Wang; Liying Pan; et al. (PLoS ONE, 2025)
Purpose The aim of this study was to investigate whether serum zinc levels correlate with the response to immune checkpoint inhibitors (ICIs) and whether they can be used as a useful prognostic biomarker in patients with advanced or metastatic cancer. Methods We divided 98 patients with advanced or metastatic lung, esophageal, gastric, and colorectal cancer into two groups based on enrollment date: the training group (n = 68) and the validation group (n = 30). And these patients were from Shandong Provincial Hospital and had received immunotherapy. We then used the solid tumor response Evaluation Criteria (RECIST v1.1) to determine whether the patient’s condition was evaluated for clinical benefit response (CBR) or non-clinical benefit (NCB). Subsequently, serum zinc levels were assessed using ICP-MS. Results We have identified for the first time that elevated levels of serum zinc (>14.2μg/L) in cancer patients undergoing immunotherapy can serve as a novel biomarker for improved overall survival (20.0m vs 10.0m; p < 0.0001), as determined by continuous serum zinc data using ROC curve analysis (sensitivity: 100.00%, specificity: 41.86%, p = 0.0009) in both CBR (n = 43) and NCB patients (n = 25) within the training group. Bioinformatics analysis has revealed that serum zinc may modulate cellular DNA replication through the MAPK and NF-kB pathways, with proteomic analysis confirming enrichment of these pathways based on KEGG and GO analyses. Consequently, a nomogram incorporating multiple clinical and independent factors has been developed to provide enhanced predictive capability. Conclusions Serum zinc levels are positively associated with the effectiveness of ICIs in patients with advanced or metastatic cancer, potentially through their modulation of NF-κB and MAPK pathways. These findings highlight serum zinc as a valuable biomarker for predicting responses to ICI treatment.